Entering a foreign labour market via the “academic gate”. The experiences of Poles who came as international students to Germany - Nina Wolfeil (Belgeo)
Against the background of debates on needs for highly-skilled labour in Germany, the article is interested in international students as a special group of Highly-Skilled Migration. It analyses the impact of studying abroad on future mobility and career patterns. The article presents results from an online survey and 27 qualitative interviews with Poles who came as international students and who later on entered the German labour market. Results from the online survey indicate that approximately 70 % return to Poland but lower return rates are observed among degree-seeking students than among exchange students. The professional value of the study abroad experience is very high. A qualitative typology comprising four types (“Brain Circulators”, “Polonia Members”, “International Career”, “Transformation Refugees”) shows how former international students combine Polish and German cultural capital in their professional life and identifies success and failed stories. As a result, special programmes should be created to smooth the transition from university to the labour market in the study abroad destination.